Webinar career talk: finding passion and resilience - Yudaruddin, Rizky; Laman, Karina Kausalya; Ambarsari, Kharisma; Chairunnisa, Putri Zhafira; Yulianti, Silvitri Diah (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2022)
Passion is defined as an affective structure, an optimistic orientation toward work that both produces and gives meaning to a variety of emotional dispositions, whereas The Oxford English Dictionary defines the contemporary use of passion as